Refining the concept of the enigmatic genus Dishkeya Stonis (Lepidoptera: Tischeriidae) upon discovery of a new species with remarkably branched leaf mines on Gouania Jacq. (Rhamnaceae) from the Amazon Basin - Stonis, Jonas R.; Diškus, Arūnas; Orlovskytė, Svetlana (Zootaxa, 2025)
This study aims to describe a new species of Dishkeya Stonis, D. tarapotica Diškus & Stonis, sp. nov., and to assess how its characteristics contribute to the morphological, biological, and molecular understanding of this small, enigmatic, and understudied genus. Despite the similarity of leaf mines between D. tarapotica sp. nov. and D. gouaniae (Stonis & Diškus), the new species is a distinct taxon that differs clearly from all other Dishkeya species—including those feeding on the same host-plant genus, Gouania Jacq. (Rhamnaceae)—due to notable differences in genital morphology. Key diagnostic characters include the small female corpus bursae, a wide male phallus with strongly developed lateral processes and exceptionally long carinae, an elaborately shaped valva, and most notably, the sclerotized socii (pseudognathos). These characters support the current concept of the genus Dishkeya. In contrast, the presence of long antennal sensilla trichodea in females of D. tarapotica sp. nov. and the related D. gouaniae represents a unique and striking trait—an atypical character within the family Tischeriidae, but one that contributes to the diagnostic characteristics of the genus Dishkeya. Molecular analysis incorporating newly generated sequences of D. tarapotica sp. nov. further confirmed its distinctiveness and once again raised the possibility that Dishkeya is more closely related to the genera Coptotrichoides Diškus & Stonis and Coptotriche Walsingham, rather than to Tischeria Zeller.